Imagining a prophetic spirituality: congregational learning for an inclusive and lived faith - Bratton, Thomas J. (2020)
Mainline Protestant congregations are struggling to adapt to the rapidly changing culture.Grounding congregants in the biblical narrative, theological reflection, and ethical practices have long been a function of local congregations. However, as American culture has become more partisan and isolated, many mainline congregations have become comfortable in their privileged place in society and have moved away from their prophetic call to do justice as a non-negotiable component of faith formation. Theproblem of separating justice and spirituality, the prophetic from the sacramental, has ledto unintended outcomes such as decline in involvement, lack of awareness of and commitment to justice concerns, and the increase of cultural/political divides. This disquisition will analyze how research-based practices of inquiry and leadership development may develop increased capacity in congregational leaders for recognizing and integrating spirituality and justice as essential components of faith formation. When congregational leaders engage in scriptural and prophetic imagination, listen to the stories of voices who have been unknown, ignored, or silenced in their communities, andpractice lived theology in their everyday, ordinary lives, they may more fully live theircalling “to do justice, love kindness, and walk humbly with God” (Micah 6:8).